056 Online assessment and monitoring of cognitive decline in neurological conditions. Issue 9 (12th August 2022) - Lerede, Annalaura; Middleton, Rodden; Rodgers, Jeff; Tuite-Dalton, Katherine; Trender, William; Hellyer, Peter; Nicholas, Richard; Hampshire, Adam
Abstract : Neurological conditions present with cognitive impairment that greatly affects the quality of life of the patients and should be routinely evaluated. However, it can be difficult to detect and impractical to monitor with classic in person cognitive assessment due to limitations of sensitivity, scalability and cost. Internet- and app-based tools for cognitive assessment are a potential solution of this problem, offering superior sensitivity and being deliverable remotely in the context of clinical registries, providing an acces- sible and cost-effective way to combine large-scale longitudinal cognitive and clinical data. To validate this idea, we administered a superset of 23 internet-deliverable cognitive tasks from the Cognitron platform to people with multiple sclerosis (PwMS) through the UKMSRegister. These tasks come with extensive normative data (N>400, 000) collected during previous large-scale studies. We report high sensitivity to cognitive deficits in PwMS and identify the cognitive domains that are most vulnerable. We propose an optimal subset of tasks that can provide an efficient multivariate profile of cognitive decline in PwMS at scale and longitudinally via MSRegisters. This same approach will be extended to other neurological conditions, offering a way to measure and predict the evolution of cognitive impairment over time, and monitor the long-term impacts of interventions.